Fee-Free Basic Education in the Democratic Republic of the Congo: Dream or Reality? - Mihigo, Isidore Murhi; Eugene, Mumbere Lubula; Akonkwa, Déogratias Bugandwa Mungu (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
The purpose of this study is to show how political discourse has influenced the introduction of free-of-charge Basic Education (FFBE) in the Democratic Republic of Congo (DRC) during the 2019-2020 school year, following President Félix Tshisekedi's election promise. This article analyses the link between political utterances on free-of-charge decision and their implementation in the provision of public services. The paper is based on an assemblage framework to analyse stakeholders in FFBE implementation. Using press articles and secondary data from official reports, we found that the obstacles in implementing FFBE may be explained by the need for a properly concise public policy about free education, the mismanagement of different stakeholders, the lack of transparency and economic constraints. The population concerned is all the stakeholders in the education system in the DCR. To arrive at our conclusion, we used the assemblage method. In DRC, the promise of FFBE faces significant challenges, notably funding shortages, inadequate infrastructure, and a lack of trained teachers. The economic instability in the region hampers government investment in educational resources, often resulting in fees being imposed by schools despite official policies promoting free education. Future research could focus on innovative funding models, such as community-based initiatives or partnerships, to enhance educational delivery. Additionally, exploring the impact of digital learning tools could provide insights into bridging educational gaps, especially in remote areas where access to traditional schooling is limited.